Commissive Speech Acts in President Prabowo Subianto's Speech at the 80th UN General Assembly: A Pragmatic Analysis - Isnaeni, Isnaeni (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study examines commissive speech acts in President Prabowo Subianto's first speech at the 80th United Nations General Assembly in 2025 using a pragmatic approach. Commissive speech acts were chosen because the speech contains many statements that demonstrate political commitments, diplomatic promises, and Indonesia's strategic plans on global issues. This study uses a qualitative descriptive method with data consisting of utterances containing commissive elements in the speech. The analysis results show that the commissives that appear include forms of promises, willingness, commitments, and long-term plan statements. These findings indicate that the speech functions not only as a means of conveying information but also as a tool to build a diplomatic image and demonstrate Indonesia's position at the international level. Overall, commissive speech acts play an important role in reinforcing the political message and policy direction that Indonesia aims to assert in the global forum.